Care of the Soul : a Guide for Cultivating Depth and Sacredness in Everyday Life - Moore, Thomas, 1940- (New York Harper Perennial, a division of HarperCollins Publishers, 1992)
A therapist draws on the world's religions, music, art, and his own experiences with patients to examine the connections between spirituality and the problems of individuals and society
Acknowledgments -- Introduction -- Care Of The Soul: -- 1. Honoring symptoms as a voice of the soul -- Care Of The Soul In Everyday Life: -- Myth of family and childhood -- Self-love and its myth: narcissus and narcissism -- Love's initiations -- Jealousy and envy: healing poisons -- Soul and power -- Gifts of depression -- Body's poetics of illness -- Economics of soul: work, money, failure, and creativity -- Spiritual Practice And Psychological depth: --
"A hardcover edition of this book was published in 1992 by HarperCollins Publishers"--Title page verso
Includes bibliographical references (pages 311-312)
Keywords: Spiritual life; Psychology, Religious; Spiritual life; Psychology, Religious; Nonfiction